Grouting failure mechanism and new pre-grouting reinforcement technology of narrow coal pillar in fully-mechanized caving gob-side entry - Dongdong Chen; Zhixuan Zhang; Shuaishuai Yue; Chunyang Tian; Qingbo Jia; Shengrong Xie; Wenkang Zhao; Jingchen Chang; Xiangyu Yang; Fuxing Xie; Hao Pan (Scientific Reports)
Abstract With the wide application of large machinery in coal mining, the influence of mine pressure is large and wide. Therefore, it is very important to retain and maintain the strength of coal pillars in the working face section. But the traditional narrow coal pillar grouting technology often causes grouting failure due to slurry leakage. In order to avoid this situation, the pre-grouting solidification technology is put forward. Through theoretical analysis and speculation, numerical simulation, field test and monitoring and other methods, this article discusses the shortcomings of traditional grouting methods, the causes of grouting failure, and the reasons for grouting failure, the characteristics of fracture distribution in narrow coal pillar, the concrete implementation method of pre-grouting solidification technology and the reasonable selection of grouting time. The results show that the high fracture development within the narrow coal pillar has good grouting permeability, and the coal pillar is pre-grouting reinforced before the excavation of the roadway along the goaf, combined with the flexible thin-layer shotcrete layer and reasonable grouting time, the solidification of narrow coal pillar has achieved good results, and has constructed a good surrounding rock environment for excavation and support of roadway.